Improving hot corrosion resistance of Cr3C2-20NiCr coatings with CNT reinforcements - Goyal, Khushdeep; Goyal, Rakesh (Surface engineering, 2020)
Carbon Nanotubes (CNT) reinforced Cr 3 C 2 -20NiCr composite coatings were prepared and deposited on alloy steel using high-velocity oxyfuel (HVOF) thermal spraying method. The comparative effects of variation in CNT content (from 1 to 2 weight percentage) on mechanical properties and hot corrosion behaviour in super-heater zone of actual coal-fired boiler of a thermal power plant at 900°C have been investigated. After exposure to boiler environment, the corrosion products have been analysed by thermogravimetric analysis, X-ray diffraction, scanning electron microscopy, energy dispersive and cross-sectional analysis techniques. The results confirmed that variation in CNT content improved the mechanical and microstructural properties of surface coatings by modifying their surface characteristics. The variation in CNT content improved the corrosion protection property of composite coating at high temperature of exposure. Reduction in corrosion rate was observed with increase in CNT content from 1 to 2 weight percentage in the Cr 3 C 2 -20NiCr coating matrix.